Optimalisasi Ekonomi Kreatif Dalam Meningkatkan Kesejahteraan Masyarakat Menurut Perspektif Ekonomi Syariah - Hidayat, Deden; Maskur, Maskur; Rohmatulloh, Puri (STAI La Tansa Mashiro, 2023)
The creative economy is one of the new economic concepts that intensifies information and creativity as well as human resources (HR) as the most important factors of production. Products produced from the creative economy are products that have characteristics, are unique, and are different from others. Products from the creative economy can also be a development of existing products. The problems raised in this study are How to optimize the Creative Economy in Bojong Menteng Village, How Creative Economy activities in Bojong Menteng Village can improve people's welfare, What are the obstacles to Creative Economy in improving welfare. The purpose of the study was to find out how to optimize the creative economy in Bojong Menteng Village. To find out how creative economy activities in Bojong menteng village improve the welfare of the community. This research is a qualitative research with a case study approach that aims to determine the creative economy in the welfare of the people in Bojong Menteng Village, Leuwidamar District, Lebak Regency. Techniques for data collection, the data used is the method of observation, interviews, documentation. And literature study. The results of the study showed that optimizing the creative economy in the welfare of the people in Bojong Menteng Village developed quite well because it could provide job opportunities for the community's economy. After the creative economy has increased little by little and has changed, although not significantly, it has been able to improve the welfare of the community through employment opportunities so that it can improve people's welfare, and reduce the number of unemployed.Keyword : Creative economy, Community welfare